The Role of Career Adaptability, the Tendency to Consider Systemic Challenges to Attain a Sustainable Development, and Hope to Improve Investments in Higher Education - Di Maggio, Ilaria; Ginevra, Maria Cristina; Santilli, Sara; Nota, Laura; Soresi, Salvatore (Frontiers in Psychology, 2020)
Based on the Life Design approach and on recent directions from the perspective of a sustainable and inclusive career guidance, the study aimed at examining the relationship between career adaptability, tendency to consider systemic challenges to attain a sustainable development, and personal and social hope, and their role in affecting the tendency to invest in higher education. The analyses carried out involving 416 Italian high school students found that career adaptability and tendency to consider systemic challenges in order to attain a sustainable development were directly and indirectly related to tendency to invest in higher education, through personal and social hope. The results obtained allowed to provide new contribution to extend results previously described by the Life Design approach in career development issues and provided useful suggestions for preventive career interventions.